The Role of Leadership on Job Satisfaction - Dewi, Ratna; Tandiawan, Vira; A, Nurnaningsih.; Tora, Ermin; Ain, Fatima Wati (SEIKO : Journal of Management & Business, 2023)
The purpose of this study is to look at the impact of leadership on employee work satisfaction at PT Golden Hill Luwuk Banggai. The sampling method is nonprobability sampling. The analysis employs Partial Least Squares (PLS) based on Structural Equation Modeling (SEM), and data is collected via a Google form questionnaire. Two variables that can be identified are used by researchers. There are three external variables in this study: leadership (X1), compensation (X2), and motivation (X3). There is one endogenous variable in this study, which is Job Satisfaction (Y). Employees at PT. Golden Hill Luwuk Banggai 141. The sample in this study was gathered using a non-probability sampling technique, hence the sample size was 102 after being computed using the Slovin formula. This study shows that leadership has a considerable positive effect on workplace satisfaction, as does work motivation. Significantly improves job satisfaction. The more the work motivation, the greater the job happiness of the PT. The Golden Hill Luwuk Banggai. Similarly, stress has a considerable positive effect on happiness. The stronger the company's protection, the happier the PT employees. The Golden Hill Luwuk Banggai. Keywoard: Leadership, Work Stress, Employee Performance